Effect of Addition of Methanol on Catalytic Activity of Polyethylene Glycols as Phase Transfer Catalyst - Saiki, Motohisa; Ido, Tadaatu; Goto, Shigeo (KAGAKU KOGAKU RONBUNSHU, 1988)
The dehydrohalogenation of 2-bromooctane in toluene (organic phase) by polyethylene glycols (phase transfer catalyst) was investigated in a batch reactor containing an aqueous solution of potassium hydroxide (aqueous phase). Reaction rates were increased by a factor of 126 at maximum by the addition of methanol. The base efficiency (moles of base per mole of catalyst) of polyethylene glycols (PEG) with molecular weights 3000 and 20, 000 exceeded unity and reached 12 at maximum by the addition of methanol.